Biodegradable gelatin/beta‐tricalcium phosphate sponges incorporating recombinant human fibroblast growth factor‐2 for treatment of recession‐type defects: A split‐mouth study in dogs. (27th March 2017) - Shujaa Addin, A.; Akizuki, T.; Hoshi, S.; Matsuura, T.; Ikawa, T.; Fukuba, S.; Matsui, M.; Tabata, Y.; Izumi, Y.
Abstract : Background and Objective: Tissue engineering by using recombinant human (rh) growth factor technology may offer a promising therapeutic approach for treatment of gingival recession. Fibroblast growth factor‐2 (FGF‐2) has shown the ability to promote periodontal regeneration. Gelatin/beta‐tricalcium phosphate (gelatin/β‐TCP) sponges have been developed to control the release of growth factors. The present study evaluated the periodontal regenerative efficacy of rhFGF‐2 by comparing gelatin/β‐TCP sponges incorporated with rhFGF‐2 to the scaffolds alone in artificially created recession‐type defects in dogs. Material and methods: Critically sized buccal gingival recession defects were surgically created on maxillary canine teeth of five dogs. In each animal, defects were randomized to receive either a gelatin/β‐TCP sponge soaked with rhFGF‐2 (gelatin/β‐TCP/rhFGF‐2) or phosphate‐buffered saline (gelatin/β‐TCP). Eight weeks after surgery, biopsy specimens were obtained and subjected to microcomputed tomography and histological analyses. Results: Complete root coverage was achieved in both groups. Microcomputed tomography revealed significantly greater new bone volume in the gelatin/β‐TCP/rhFGF‐2 group. Histologically, both groups achieved periodontal regeneration; however, gelatin/β‐TCP/rhFGF‐2 sites exhibited more tissue regeneration, characterized by significantly larger amounts of new cementum and new bone. Gelatin/β‐TCP sites featured increased long junctional epithelium and connective tissue attachment. In the gelatin/β‐TCP/rhFGF‐2 sites, new bone exhibited many haversian canals and circumferential lamellae as well as remarkably thick periosteum with blood vascularization and hypercellularity. Conclusion: Within the limitations of this study, rhFGF‐2 in gelatin/β‐TCP sponges exhibits an increased potential to support periodontal wound healing/regeneration in canine recession‐type defects.